The Effect Of Student Type of Student Teams Achievement Divisions (STAD) and Jigsaw On Economic Learning Achievement - I Gusti Putu Endra Suantara (Pedir Research Institute, 2022)
The objective of this research are to investigate: (1) the effect of the cooperative learning model of the Student Teams Achievement Divisions (STAD) and Jigsaw types on the learning achievement in Economics; (2) the effect of the students’ high and low learning motivations on the learning achievement in Economics; and (3) the interaction between the effect of the learning models and the learning motivations on the learning achievement in Economics. This research used the quantitative experimental research method. Its population was all of the students of Senior Secondary Schools of 2 Mendoyo. The samples of research were taken by using the simple random sampling technique and consisted of 70 students, namely: 36 students in Grade X2 of State Senior Secondary School of 2 Mendoyo as the experimental class instructed with the cooperative learning model of the STAD type and 34 students in Grade X1 of State Senior Secondary School of 2 Mendoyo as the control class instructed with the cooperative learning model of the Jigsaw type. The data of research were collected through documentation, questionnaire and test. They were analyzed by using the two-way analysis of variance with unbalanced cells with the prerequisite tests of normality test and homogeneity test. The factorial design was 2x2 at the significance level of 0.05. The test calculation was aided with the computer program of Software SPSS 23. The results of research show that: (1) there is a different of effect between the cooperative learning model of the STAD type and that of the Jigsaw type on the learning achievement in Economics as indicated by the significance value = 0.00 which is smaller than α = 0.05 or (Fobs = 10.103 > Ftable = 4.00); (2) there was a different of effect between the students’ high learning motivation and the students’ low learning motivation on the learning achievement in Economics as shown by the significance value = 0.00 which is smaller than α = 005 or (Fobs = 57.338 > Ftable = 4.00); and (3) there was not any interaction between the effect of the learning models and the that of the students’ learning motivations on the learning achievement in Economics as specified by the significance value = 0.517 which is greater than α = 0.05 or (Fobs = 0.425 < Ftable = 4.00).